Reduced Translocation of Glyphosate and Dicamba in Combination Contributes to Poor Control of Kochia scoparia: Evidence of Herbicide Antagonism - Ou, Junjun; Thompson, Curtis R.; Stahlman, Phillip W.; Bloedow, Nicholas; Jugulam,Mithila (My University, 2018)
Kochia scoparia is a troublesome weed across the Great Plains of North America. Glyphosate and dicamba have been used for decades to control K. scoparia. Due to extensive selection, glyphosate- and dicamba-resistant (GDR) K. scoparia have evolved in the USA. Herbicide mixtures are routinely used to improve weed control. Herbicide interactions if result in an antagonistic effect can significantly affect the management of weeds, such as K. scoparia. To uncover the interaction of glyphosate and dicamba when applied in combination in K. scoparia management the efficacies of different doses of glyphosate plus dicamba were evaluated under greenhouse and field conditions using GDR and a known glyphosate- and dicamba-susceptible (GDS) K. scoparia. The results of greenhouse and field studies suggest that the combination of glyphosate and dicamba application controlled GDS, but glyphosate alone provided a better control of GDR K. scoparia compared to glyphosate plus dicamba combinations. Furthermore, investigation of the basis of this response suggested glyphosate and dicamba interact antagonistically and consequently, the translocation of both herbicides was significantly reduced resulting in poor control of K. scoparia. Therefore, a combination of glyphosate plus dicamba may not be a viable option to control GDR K. scoparia.
Citation: Ou, Junjun, Curtis R. Thompson, Phillip W. Stahlman, Nicholas Bloedow, and Mithila Jugulam. “Reduced Translocation of Glyphosate and Dicamba in Combination Contributes to Poor Control of Kochia Scoparia : Evidence of Herbicide Antagonism.” Scientific Reports 8, no. 1 (March 28, 2018): 1–11. https://doi.org/10.1038/s41598-018-23742-3.
Keywords: Abiotic; Plant physiology